THE RESTING MODELS DURING TRAINING THAT AFFECTS THE ABILITY TO MOVE IN MULTIPLE MOVEMENTS OF THAI WOMEN’S NATIONAL TEAM KABADDI ATHLETES - Phonchoo, Tin; Tengku Sulaiman, Raja Syed; Sriwisut , Panu (Academic Journal of Thailand National Sports University, 2022)
The purpose of this study was to study the relationship and compare the multi movements performance and heart recovery rate of the Thai women’s national Kabaddi team athletes after the simulated competition training. The three resting models consisted of regular rest, rest with stretching, and rest with cold water stroking which were used in this study. The samples used in this study were the 30 Thai women’s national Kabaddi team athletes with similar abilities from Krabi National Kabaddi Team Center. The samples as mentioned were selected utilizing the purposive method. After that, the samples were randomly divided into 3 experimental groups. The instruments used to collect the data were a heart rate measurement and a multi movements performance test. The statistics for the data analysis were mean, standard deviation, Pearson Product - Moment Correlation coefficient, one - way ANOVA and Bonferroni multiple comparison test (Bonferroni’s test). The significance level was set at 0.05. The results showed that there are significant relationships between the multi movements performance and the heart recovery rate of all experimental groups at the .05 level. More Specifically, this study was also found that the rest with cold water stroking was the most effective model to speed up the heart recovery rate of the Thai women’s national Kabaddi team athletes, followed by the rest with stretching and regular rest respectively.